2008
DOI: 10.1002/da.20363
|View full text |Cite
|
Sign up to set email alerts
|

Hypomanic symptoms predict an increase in narcissistic and histrionic personality disorder features in suicidal young adults

Abstract: Consistent with the "scar hypothesis", according to which mood depression might impact personality, we examined the effect of unipolar and hypomanic mood disturbances on cluster B (i.e., narcissistic, histrionic, and borderline) personality disorder features. Data from 113 suicidal young adults were utilized, and cross-lagged associations between unipolar and hypomanic mood disturbances and cluster B personality disorder features were examined using manifest-variable structural equation modeling (SEM). Hypoman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Indeed, the importance of histrionic PD in the course of BSDs may be under-recognized, as it is one of the most prevalent PDs in BSDs (George et al, 2003). Moreover, hypomanic symptoms have been shown to predict an increase in histrionic PD symptoms prospectively (Shahar et al, 2008), suggesting that hypomanic symptoms may exacerbate histrionic PD symptoms, which, according to the results of the current study, may be associated with increased risk for experiencing prospective hypomanic episodes and developing bipolar I disorder. Therefore, there may be an escalating vicious cycle whereby histrionic PD symptoms leads to increased hypomanic symptoms, which can further exacerbate histrionic PD symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, the importance of histrionic PD in the course of BSDs may be under-recognized, as it is one of the most prevalent PDs in BSDs (George et al, 2003). Moreover, hypomanic symptoms have been shown to predict an increase in histrionic PD symptoms prospectively (Shahar et al, 2008), suggesting that hypomanic symptoms may exacerbate histrionic PD symptoms, which, according to the results of the current study, may be associated with increased risk for experiencing prospective hypomanic episodes and developing bipolar I disorder. Therefore, there may be an escalating vicious cycle whereby histrionic PD symptoms leads to increased hypomanic symptoms, which can further exacerbate histrionic PD symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, recent findings suggest that depression is better conceptualized as a dimensional clinical condition (e.g., Hankin, Fraley, Leahey, & Waldman, 2005), which in turn indicates the importance of testing the effect of depressive symptoms on personality/self-concept using continuous depression measures. When this is done, the evidence for a depressogenic effect is mixed (for supportive evidence see Shahar, Blatt, Zuroff, Kuperminck, & Leadbeater, 2004b;Shahar & Davidson, 2003;Shahar, Scotti, Joiner, & Rudd, 2008; for null results see Hawley, Ho, Zuroff, & Blatt, 2006;Ormel, Oldehinkel, & Vollenberg, 2004;Orth, Robins, & Roberts, 2008;Shea et al, 1996). The purpose of the present study was to further elucidate this confusing pattern of results by employing a developmental perspective on depressive scarring.…”
mentioning
confidence: 96%
“…Such heterogeneity, depicted in Table 1, pertains to participants' age (e.g., adolescent vs. young adults vs. the elderly), their clinical status (e.g., non-clinical university students vs. community residents vs. people with severe mental illness), and design characteristics (i.e., considerable variability in terms of the interval time employed for assessing the longitudinal associations between depression and personality/self-concept variables). Another source of heterogeneity pertains to the putative outcome of depressive scarring, ranging from general cognitions (e.g., Lewinsohn et al, 1981), to personality-disorder features (e.g., Shahar et al, 2008), to self-concept variables such as self-criticism (Shahar et al, 2004b) or self-esteem (Ormel et al, 2004;Orth et al, 2008;Shahar & Davidson, 2003). This heterogeneity renders a general inference as to the viability of depressive scarring difficult.…”
mentioning
confidence: 98%
“…However in one study it was found that hypomanic symptoms predicted an increase in histrionic personality disorder features (Shahar 2008).…”
Section: Precursor Symptomsmentioning
confidence: 97%